Reynolds number calculation method for aerobic biological porous packed reactors - Fatihah Suja’,; Tom Donnelly, (2006)
The degree of mixing in aerobic biological porous packed reactors can be quantitatively determined by Reynolds Numbers calculation. The dimensionless parameter accounts for all the inertial and viscous forces in the fully and partially packed reactors. Two identical reactors were built; each reactor was 14 cm in diameter and 100 cm in height, providing an empty bed volume of 15 L. At approximate organic loading rates (OLRs) of 2, 3, 4, and 6 kg COD/m3.d, the Reynolds numbers in the partial-bed were 40 300, 36 100, 25 500 and 40 400 respectively, whilst those of the full-bed were 19 500, 20 500, 11 700 and 26 400. The quantity of media therefore had a significant effect on the extent of mixing in the filter. Porosity of the aerobic porous packed reactors is a bed characteristic resulting from the balance between the effect of biomass accumulation due to growth and biomass loss due to shear stress. The stress arises from increased organic loadings and increased upflow velocity due to aeration